Preventing Relapse into Drug Crime through Motivational Talks at a Drug Scene in Stockholm<subtitle>A Randomised Controlled Trial of a Law Enforcement Tactic</subtitle> - Mia-Maria Magnusson (Nordic Journal of Studies in Policing)
A randomised controlled trial was developed and implemented together with police officers working to combat drug crime at an open drug scene in Stockholm. The aim was to evaluate a method called motivational talks, which are held by police officers to encourage drug crime suspects to seek help. Relapse into drug crime was compared between the control group and the experimental group to determine whether the treatment, i.e., the motivational talk, had an effect. The study shows that motivational talks had a small but non-significant impact on relapse into drug crime after nine months, but the effect had disappeared at the second follow-up. Motivational talks might still have other effects on the individual or the police. Studying the use of repeated treatment might be a way of furthering the research on the effect of motivational talks.